Urgency of Extradition Agreements in Eradicating Corruption Crime in Indonesia - Andi Rachmad; Zaki Ulya; Yusi Amdani (Fakultas Hukum Universitas Mataram, 2022)
Corruption is a special crime that is very detrimental to the country. Corruption management has been upheld by law enforcement in the framework of guaranteeing the state’s stability. Changes to the regulation on corruption eradication does not reduce the number of corruption penalties and compensation for assistance that is free from the snares of the law. This is what drives the government to make an extradition treaty with Singapore and ensnare corruption protection that can be done in Indonesia. This study discusses and examines the level of urgency of the extradition treaty in efforts to commit corruption between Indonesia and Singapore. And, challenges and efforts in realizing the extradition agreement between Indonesia and Singapore in the approval of the implementation of corruption